Media Pendidikan Gizi dalam Mengenali dan Mengatur Makanan Cegah Balita Gizi Kurang - Dini Junita; Arnati Wulansari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Abstract Posyandu is a form of Community-Based Health Efforts (UKBM) which is managed by the community, especially in monitoring nutritional status. Nutrition status monitoring is important because nutrition influences brain development and behavior, work ability and productivity as well as resistance to infectious diseases. Toddlers are an age group that cannot yet manage their own food so parents need supervision, a group of toddlers vulnerable to malnutrition. So that the proper way of Infant and Child Feeding (PMBA) is important to be socialized. The implementation method is in the form of counseling, discussion, practice simulation and pre-post test evaluation. Evaluation monitoring is carried out by looking at indicators of success in the aspect of attendance of targets attending each meeting at the service activities and practices to the target, reflection and feedback from participants as well as PMBA practice behavior can be implemented by the target. After education, there is an increase in the ability of mothers to practice PMBA simulations. It was concluded that the use of media in providing information to mothers is very effective in increasing the ability of mothers in the correct PMBA so that it is expected to reduce nutritional problems in children. A program that is continuous with supervision by health workers and involves cadres in providing information to mothers of toddlers needs to be done.